(untitled) (TAMADDUN NURI JURNALI, 2024)
The article explores the intricate relationship between the author’s identity and the unique narrative style of psychological thrillers, focusing on Harris’s iconic Hannibal Lecter series comprising “Red Dragon”, “The Silence of the Lambs”, “Hannibal”, and “Hannibal Rising”.